Model Guide Discovery Learning terhadap Kemampuan Komunikasi Matematis - Khairunnisa’ Nabilah; Mutiara Khadijah; Kania Utari (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Mathematics plays an important role in developing a systematic, rational, and critical mindset, as well as the development of contemporary science, science, and technology. This study discusses the importance of the ability to communicate mathematically in the context of mathematics learning and to find errors in mathematical communication in everyday situations, especially in terms of understanding the concept of fractional numbers. The purpose of this study is to improve the understanding of mathematical communication skills by using Guided Discovery Learning model. Secondary data were collected from articles and journals related to the Guided Discovery Learning model in this study. This model is considered as a solution to improve students' mathematical communication skills by actively involving them in discovering and understanding mathematical concepts. The literature method was used in this study. Understanding the concept of fractions, measuring mathematical communication skills, and analyzing mathematical communication errors in daily conversations are the topics of discussion. This research shows that mathematical communication skills are very important in learning mathematics, and the Guided Discovery Learning model can help students discover things by themselves. In conclusion, this study highlights the importance of mathematical communication skills in mathematics learning and suggests Guided Discovery Learning model as an effective method to improve mathematical communication skills.